رقابة القاضي الإداري للأنشطة الاتفاقية أو الإرادية - وناس, يحي (جامعة الوادي university of eloued, 2016)
دفعت التحولات الحالية بالدولة إلى التوجه إلى اختيار الأنشطة الاتفاقية المرنة. وبتزايد اللجوء إلى هذه الأساليب ظهرت انحرافات وتجاوزات كثيرة مست وحدة المنظومة القانونية والمشروعية والمساس بالحقوق. ونتيجة لذلك أرسى القضاء خلال فحصه لبعض الأنشطة أسس هذه الأنشطة، وفرض احترام المشروعية والحقوق والحريات في اعتماد هذه الأنشطة. Current changes have obliged the state to turn to choose flexible agreement activities. As a result of the increasing resort to these methods many deflections and abuses have appeared and touched the unity of legal system, the rights of legitimacy and prejudice to the rights. As a result, during the examination of some of the activities, the judiciary has laid the foundations for these activities, and it has imposed the legitimacy and respect for the rights and freedoms in the adoption of these activities
مقال
Keywords: رقابة – القاضي الإداري – نشاط اتفاقي – المشروعية; Control - administrative judge - Activity Agreements - legitimacy